Pengaruh Kompetensi Sumber Daya Manusia dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Penyajian Laporan Keuangan - Muhammad Titan Terzaghi; Poppy Indriani; Haerleyawan Setya (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
This research intended to explore the effect of the competence of human resource and the use of technology information to financial report quality. The object of this research was SKPD Government of Empat Lawang Regency of South Sumatera Province. Sample in the research amounted to 39 samples of employees. The results showed that the competence of human resources significantly positive impact on the quality of financial statement presentation. While on the utilization of information technology had no significant effect. By adding financial accountability as a moderator variable, the R Square competency variable of human resources rose by 0.203 or 20.3%. Then on variable utilization of information technology equal to 0,140 or 14%. It could be concluded that with the existence of financial accountability would be able to strengthen the relationship between the competence of human resources and utilization of information technology to the quality of financial presentation.